This can be displayed as a system of equations.
x = 3 + 5y
x - y = 11
Because we have a value of x we can plug it into the value of x in the second equation.
(3 + 5y) - y = 11
3 + 5y - y = 11
Combine like terms.
3 + 4y = 11
Subtract 3 from both sides.
4y = 8
Divide both sides by 4.
y = 2
Now that we have a constant value for y, we can replace the value of y in the second equation with 2 to solve for x.
x - 2 = 11
Add 2 to both sides.
x = 13
Now, let's verify.
13 = 3 + 5(2)
13 = 3 + 10
13 = 13 √ this is correct.
13 - 2 = 11
11 = 11 √ this is correct.
The first number, or x, is equal to 13.
The second number, or y, is equal to 2.